A Hybrid RFOA-DDAO Based Voltage Transfer Gain Enhancement through Ultra Lift Luo Converter and Cockcroft-Walton Multiplier - Merlin Suba, G.; Kumerasen, M. (International Journal of Intelligent Systems and Applications in Engineering, 2022)
This manuscript proposes a novel hybrid strategy to enhance the voltage gain through an ultra-lift luo converter and cockcroft-walton multiplier for driving electric vehicles smoothly. The proposed hybrid strategy is the joint execution of Red Fox Optimization Algorithm (RFOA) and Dynamic Differential Annealed Optimization (DDAO) and hence it is named as RFOA-DDAO system that creates the greater voltage transfer gain. Entire world is focusing towards electric vehicle to reduce CO2 level in the environment. All renewable energy sources are of low voltage but it is not enough to drive electric vehicle. So we need interfacing equipment as converter to enlarge the voltage gain from low voltage to high voltage to drive electric vehicle. Here, an output voltage variation as well as voltage deviation can be minimized using this proposed technique. Finally, the proposed approach is executed on MATLAB/Simulink working platform and execution result is compared with the existing techniques like BOA and GPC methods.